2021
DOI: 10.1126/science.abe1544
|View full text |Cite
|
Sign up to set email alerts
|

Landmarks of human embryonic development inscribed in somatic mutations

Abstract: Although cell lineage information is fundamental to understanding organismal development, very little direct information is available for humans. We performed high-depth (250×) whole-genome sequencing of multiple tissues from three individuals to identify hundreds of somatic single-nucleotide variants (sSNVs). Using these variants as “endogenous barcodes” in single cells, we reconstructed early embryonic cell divisions. Targeted sequencing of clonal sSNVs in different organs (about 25,000×) and in more than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 41 publications
5
86
0
Order By: Relevance
“…The cancer field commonly uses the presence or absence of somatic mutations in clonal populations to track the evolutionary history of a tumor 24,25 . Recent studies have expanded on this approach to use somatic mutations as endogenous barcodes to track embryonic development 26 . Using this same approach, we infer that the DVA was the first lesion to develop and that the associated CCM is derived from cells of the DVA following a somatic mutation in MAP3K3.…”
Section: Resultsmentioning
confidence: 99%
“…The cancer field commonly uses the presence or absence of somatic mutations in clonal populations to track the evolutionary history of a tumor 24,25 . Recent studies have expanded on this approach to use somatic mutations as endogenous barcodes to track embryonic development 26 . Using this same approach, we infer that the DVA was the first lesion to develop and that the associated CCM is derived from cells of the DVA following a somatic mutation in MAP3K3.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers performed high-depth whole-genome sequencing (WGS) in different human tissues to identify large numbers of somatic single-nucleotide variants (sSNVs). Based on the use of these variants as barcodes, both studies reconstructed an early embryonic development lineage and revealed that there was an asymmetric partitioning of early progenitors, and a subset of effective progenitor pools made contributions during blastula formation, gastrulation, and organogenesis [ 47 ].…”
Section: New Single-cell Techniques Address Hsc Generation At Spatial and Temporal Resolutionsmentioning
confidence: 99%
“…Synthetic lineage barcoding, which relies on gene editing technologies to induce mutations, has been implemented in a variety of model systems including the zebrafish [4][5][6][7], fruit fly [8], and mouse [9][10][11]. Natural lineage barcoding, which relies on naturally-accumulating somatic mutations, has been primarily used in humans [12][13][14][15]. And while the mechanism, timing, and extent of mutagenesis differ between various implementations, the functional outcome remains the same: genomic barcodes that can retrospectively inform cell phylogeny within one organism at a single-cell resolution.…”
Section: Introductionmentioning
confidence: 99%